Design and analysis of NCO-based OFDM model. (12th December 2011) - Veena, M.B.; Swamy, M.N. Shanmukha
Today's communication standards, such as Hiperlan/2, IEEE 802.11a/g, IEEE 802.16 and DVB, already use OFDM for digital modulation. In this work, OFDM modulator and demodulator is designed using NCO-based logic. NCO designed can generate several frequencies that are required as per OFDM standards and supports 64, 32 and 16 subcarrier applications. The OFDM modulator and demodulator designed is modelled and validated against OFDM modulator with FFT logic. The NCO-based OFDM model reduces the computation time, thus improving latency and throughput. The NCO-based OFDM model is designed to operate with a sample time of 33 µ sec, and spurious free dynamic range of 48 dBc, frequency resolution of 30.5176 MHz. A channel with SNR of 60 dB is used for verification of developed OFDM model.